Health and nutritional status of HIV infected children living in the orphanages of Rajamahendravaram, Andhra Pradesh, India - Palla, Jayasree; Mallipudi, Aparna; Komaram, Ravi Babu; S. K., Mishra (International Journal Of Community Medicine And Public Health, 2020)
Background: HIV infected orphan children are the most vulnerable and neglected group in the society. They are more susceptible to constant illness, malnutrition and social discrimination. Aim: To assess the health and nutritional status of HIV infected children living in the orphanages of Rajamahendravaram. Methods: This was a community based cross-sectional study, conducted among the HIV infected children aged 1 to 15 years, living at two orphanages in Rajamahendravaram. Study subjects were selected by consecutive sampling method. A semi-structured schedule was used for the collection of data. Health status was assessed by a schedule for morbidity profile; Nutritional status was assessed by anthropometric measurements, clinical examination and by a schedule for dietary intake. Z scores were calculated using the anthropometric measurements of the study participants; WHO reference growth charts were used to assess the nutritional status. Results were presented as percentages, proportions, mean and standard deviation. Results: Total 150 HIV infected children were enrolled in the study. The mean age of children was 9.28±2.88 years. 26% of children were born with birth weight <2.5 kg. Out of 150 children, 46.65% were underweight, 50% were stunted, and 22.6% were thin. The mean energy intake of HIV infected children indicates deficiency in comparison to reference standards of WHO. Conclusions: Unhealthy condition and undernutrition is highly prevalent in HIV infected children living in orphanages. Hence, their needs are to be addressed and all efforts need to be directed at alleviating undernutrition and ill health.